Penyuluhan dan Pelatihan Pembuatan Sabun Cair Lengkuas Di Kelurahan Sukamulya - Faizah Suryani; Selvia Afrilyanti; Manisah Manisah (IKRA-ITH ABDIMAS, 2023)
Improving social welfare can be done with various approaches, by empowering the community.Empowering PKK RT 02 women in Sukamulya Village, Sematang Borang District through training andassistance in the production of liquid soap from galangal. This activity is carried out in order to increase humanresources who are able to rely on their own strength. The specific goals and targets to be achieved in thisactivity are that PKK RT 02 women are interested and motivated to become entrepreneurship, form groupsof PKK members who become economically independent by producing liquid bath soap from galangal, andmake PKK RT 02 in Sukamulya Village stronger, more productive, creative, and responsive. To achieve thisgoal, the community service team of the Industrial Engineering Study Program has provided counseling,training and assistance to PKK women in producing liquid soap from galangal. PKK women were givenknowledge about entrepreneurs and home-based business opportunities, as well as the basic principles ofproduction. PKK women were also given training on howto make liquid bath soap from galangal, as well asproduct packaging and marketing techniques.